2015
DOI: 10.3109/17453674.2015.1123569
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an automated and marker-free CT-based spatial analysis method (CTSA) for assessment of femoral hip implant migration In vitro accuracy and precision comparable to that of radiostereometric analysis (RSA)

Abstract: Background and purpose — We developed a marker-free automated CT-based spatial analysis (CTSA) method to detect stem-bone migration in consecutive CT datasets and assessed the accuracy and precision in vitro. Our aim was to demonstrate that in vitro accuracy and precision of CTSA is comparable to that of radiostereometric analysis (RSA).Material and methods — Stem and bone were segmented in 2 CT datasets and both were registered pairwise. The resulting rigid transformations were compared and transferred to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…The MEs of rigid body registration between the RSA and CT volumes in this study are of the same order of magnitude as ME for clinical RSA trials, indicating that, from a standpoint of quality of input data, it would be feasible to continue monitoring patients with tantalum beads. It might be possible to start new migration studies using CT if one lacks a facility for RSA radiographs [ 16 , 29 ]. As stated in the introduction, the effective radiation dose of CT scans is constantly being lowered and the quality of the scans with regard to metal artifacts is improving [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MEs of rigid body registration between the RSA and CT volumes in this study are of the same order of magnitude as ME for clinical RSA trials, indicating that, from a standpoint of quality of input data, it would be feasible to continue monitoring patients with tantalum beads. It might be possible to start new migration studies using CT if one lacks a facility for RSA radiographs [ 16 , 29 ]. As stated in the introduction, the effective radiation dose of CT scans is constantly being lowered and the quality of the scans with regard to metal artifacts is improving [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the CT data to produce the 3D CT datasets and the comparison of these datasets with the RSA datasets were both performed using a previously described and validated 3D volume fusion (spatial registration) tool [ 12 , 28 , 29 ]. This semiautomated tool provides landmark-based fusion of two volumes, registering a “target” volume to a “reference” volume by exploiting cohomologous landmarks in each volume, via a variety of 3D transform modules, ranging from simple rigid body to 3D warping and including user-defined transformations.…”
Section: Methodsmentioning
confidence: 99%
“…This combined with increases in computer processing power means that CT now can form the basis for an alternative method to measure implant migration while mitigating the aforementioned limitations of RSA. Early phantom studies and clinical pilots have indicated that with methods using CT scans, a precision comparable to that of RSA can be achieved (Brodén et al 2016, Scheerlinck et al 2016 Lately, commercial image-registration software named "CTbased implant Motion Analysis" (CTMA, Sectra, Linköping) has been developed to assess implant migration using standard clinical CT scanners. This article explores the CTMA tool in a clinical setting, using 3 different types of hip cups (2 cemented and 1 uncemented) drawn from different centers in Sweden to evaluate the precision of this technique.…”
mentioning
confidence: 99%
“…Current studies evaluate computed tomography (CT) as an alternative measurement tool to RSA to analyze implant migration. They describe comparable accuracy and precision values for CT-based methods, especially in experimental settings [ 41 44 ]. Moreover, CT-based migration measurement could handle some disadvantages of RSA: CT is available in almost every hospital, picture acquisition does not require a special setup or briefed personnel, migration in all directions can be calculated, and there is no problem of marker occlusion by the implant [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a lack of clinical trials and long-term examinations evaluating CT-based migration measurement. Besides, there are still some problems to deal with, as for example artifacts of metallic implants, the influence of soft tissue or the immobilization of patients during CT scanning [ 44 ]. In summary, CT-based methods need further validation before they can be considered as an alternative to gold standard RSA.…”
Section: Discussionmentioning
confidence: 99%